Echnologies of Ethical Education of Students on the Basis of National Spiritual Heritage - U. J Ochilov (International Journal on Integrated Education, 2022)
The article provides for the use of the spiritual heritage of Central Asian thinkers in the education of schoolchildren through socialization and the formation of positive criteria in the younger generation. There are also examples from the works of great scientists, the creative path and life of each of whom is an excellent school for young people.